Application of inverse analysis in electromagnetic grinding of brown coal to obtain an optimal particle size distribution- a heuristic approach - Gandor, Michał; Sławiński, Krzysztof; Knaś, Krzysztof; Balt, Barbara; Nowak, Wojciech (Computer Assisted Methods in Engineering and Science, 2017)
This paper presents the research results of milling process optimization in the electromagnetic mill to obtain the predetermined particle size distribution of brown coal. Because of an important role of brown coal in Polish energy industry (power plants produce 9433 MW of electrical power from brown coal, which corresponds to about 34% share in total fuel usage structure of energy industry in Poland-2nd quarter 2013 [1]), there is a great need to look for and develop highly efficient methods of its mining, valorisation and low-emission combustion alongside with CO 2 capture technology. This paper proposes, as one of the methods of adapting low-rank coal to being utilized in modernized and newly built plants, the process of simultaneous grinding and drying in an electromagnetic mill system. This method is energy efficient and what is more significant it reduces the space required for its adaptation, thanks to electromagnetic mill's compact installation design. It is essential to obtain the desired characteristics of the product through the adequate control of the processes. Major concern of this case study was focused on determination of optimal grinding parameters in the electromagnetic mill in order to obtain two products of a desired size distribution (1-6.3 mm for application in fluidized bed boilers and 0-315 µm for boiler burners). The authors presented some theoretical considerations of the mechanisms and physical phenomena occurring during a fragmentation of solid particles as well as the literature review of the subject. The process complexity level, taking place in the active area of electromagnetic mill, involves the influence of particle-milling rod and particle-particle interactions as well as the volume of milling rods or coal particle residence time on the size distribution of the product. All of the mentioned factors account for nonlinearity of the problem and make the conditions difficult to rescale. Hence, a heuristic approach to inverse problem was chosen to analyse the differences between the desired and obtained particle size distributions. The examinations concerned grinding parameters such as total amount of rods (volume-based) and rod sizes (single and multi-size combinations of milling elements) were conducted. Equivalent samples of Polish brown coal with a particle diameter size ranging from 0 to 10 mm were chosen as an investigated material. Influence of the total volume of rods was examined using three amounts: 100 ml, 150 ml and 200 ml. Two grinding aid sizes were chosen in the form of ferromagnetic rods: fine rods of the size of 10 x 1 mm and coarse rods of the size of 20 x 2 mm.